COVID-19-Related Psychosocial Care in General Hospitals: Results of an Online Survey of Psychosomatic, Psychiatric, and Psychological Consultation and Liaison Services in Germany, Austria, and Switzerland - Schaefert, Rainer; Stein, Barbara; Meinlschmidt, Gunther; Roemmel, Noa; Huber, Christian G.; Hepp, Urs; Saillant, Stéphane; Fazekas, Christian; Vitinius, Frank (Frontiers in Psychiatry, 2022)
Trial registration: ClinicalTrials.gov NCT04753242, version February 11, 2021 Background: The Coronavirus disease 2019 (COVID-19) pandemic was accompanied by new challenges for psychosocial health care to enable support of affected patients, their families, and staff in general hospitals. In this study, we aimed to describe the structures and procedures put in place by psychosomatic, psychiatric, and psychological consultation and liaison (CL) services in German, Austrian, and Swiss general hospitals, and to elucidate emerging needs for cooperation, networking, and improvement. Methods: We conducted a cross-sectional online survey between December 2020 and May 2021, using a 25-item questionnaire derived from relevant literature, professional experience, and consultation with the participating professional societies. The survey was disseminated via national professional societies, relevant working and interest groups, and heads of the above-mentioned CL services. Results: We included responses from 98 CL services into the analyses, with a total response rate of 55% of surveyed hospital CL services; 52 responses originated from Germany, 20 from Austria, and 26 from Switzerland. 77 (79%) of the 98 responding CL services reported that “COVID-19 related psychosocial care” (COVID-psyCare) was provided in their hospital. Amongst these, 47 CL services (61%) indicated that specific cooperation structures for COVID-psyCare had been established within the hospital. 26 CL services (34%) reported providing specific COVID-psyCare for patients, 19 (25%) for relatives, and 46 (60%) for staff, with 61%, 12%, and 27% of time resources invested for these target groups, respectively. Regarding emerging needs, 37 (48%) CL services expressed wishes for mutual exchange and support regarding COVID-psyCare, and 39 (51%) suggested future changes or improvements that they considered essential. Conclusion: More than three-quarters of participating CL services provided COVID-psyCare for patients, their relatives, or staff. The high prevalence of COVID-psyCare services targeting hospital staff emphasizes the liaison function of CL services and indicates the increased psychosocial strain of healthcare personnel during the COVID-19 pandemic. Future development of COVID-psyCare warrants intensified intra- and interinstitutional exchange and support.